PERTUMBUHAN UDANG VANNAMEI (Litopenaeus vannamei) DI TAMBAK INTENSIF DENGAN MANAJEMEN PLANKTON SEBAGAI PENYEIMBANG EKOSISTEM - Raden Muhammad Minanur Rohman Al Mubarok; Farikhah Farikhah (Jurnal Perikanan Pantura (JPP), 2024)
Cultivating vannamei shrimp (Litopenaeus vannamei) in intensive ponds is one of the efforts to meet the high market demand. This research aims to analyze the weight growth and daily weight growth rate of intensively cultured vannamei shrimp. The study was conducted in two groups of PT-owned intensive shrimp ponds.STP with different stocking densities. The research was carried out for three months, from September to November 2023. The variables of this study included Average Body Weight (ABW), Average Daily Growth (ADG), and Specific Growth Rate (SGR) of cultured shrimp. The research data were analyzed using Microsoft Excel 2023 and further analyzed using a t-test with a significance level 0.05. The results of this study showed that shrimp ponds in group II performed better, with an average shrimp weight of 4.26±0.10 gram, a daily growth rate of 0.147gram/day, and a specific growth rate of 14.73%±1% bw/day. These values were higher than shrimp cultured in group I ponds, which had an average shrimp weight of 4.14±0.25 gram, a daily growth rate of 0.148 gram/day, and a specific growth rate of 14.8%±2% bw/day.